DNA barcodes, morphology and geographic distribution confirm a new butterfly species in the genus Rhamma (Lepidoptera: Lycaenidae) - Prieto, Carlos; Hincapie, Carlos Federico Álvarez; Giraldo, Alejandra Clavijo; Uribe, Sandra (Zootaxa, 2020)
We diagnose a new butterfly species from the Belmira paramo in the central cordillera of the Colombian Andes. We infer from the barcoding analysis, wing pattern, morphology and distribution that this entity is not a geographical variation or subspecies of any named lycaenid, and it is described herein as Rhamma eleonorae sp. nov. Adult specimens and female genitalia are illustrated and compared with R. arria (Hewitson, 1870) and R. oxida (Hewitson, 1870), the most closely related taxa based on similarities of wing pattern and COI sequences.